Critique of Spiritual Concepts in Transpersonal Psychology and Their Interrelation with The Qur’ān - Sri Haryanto; Mohammad Muslih (Journal of Islamic Thought and Civilization, 2024)
Spirituality holds a significant position within transpersonal psychology, where it is deemed crucial for individual development and psychological well-being. This research conducts a critical analysis of spiritual concepts within transpersonal psychology vis-à-vis the teachings of the Al-Qur'ān. The primary aim of this research is to delineate the similarities and disparities in the understanding of spirituality between transpersonal psychology and Qur’ānic concept of spirituality through an in-depth examination of literature and theoretical perspectives. The outcomes of this study are intended to highlight the importance of comprehending the multifaceted and diverse interpretations of spirituality across various contexts. In addition, a content analysis approach will be employed in this study, in which the gathered data will be meticulously screened. This research finds out that transpersonal psychology places spirituality as a central theme in its studies. In transpersonal psychology, spirituality refers more to human aspirations for a meaningful life and as a source of human qualities. In other words, spirituality in the transpersonal psychology conception focuses more on aspects of human spirituality without touching on broader spiritual dimensions as taught in religions. While Qur’ānic concept of spirituality encompasses more than just their inner attributes that are connected to transcendental objects; it also includes their spirit's essence and existence, which has a unique purpose that transcends their physical function, reason, and soul.